FRI0486 Intravenous golimumab in adult patients with active psoriatic arthritis: efficacy and safety through week 24. (15th June 2017) - Kavanaugh, A; Husni, ME; Harrison, DD; Kim, L; Lo, KH; Hsia, EC
Abstract : Objectives: The GO-VIBRANT study was designed to evaluate the safety and efficacy of intravenous (IV) golimumab (GLM) in adult patients (pts) with active PsA (biologic-naïve). Methods: GO-VIBRANT is a Phase 3, multicenter, randomized, double-blind, placebo (PBO)-controlled trial. Biologic-naïve active PsA pts were randomized (1:1) to IV GLM 2mg/kg at weeks (wk) 0, 4, and every 8 wks thereafter or PBO at wks 0, 4, 12, and 20 with crossover to GLM at wk24. The primary endpoint was ACR20 response at wk14. Multiplicity-controlled endpoints were ACR50, ACR70, PASI 75, change from baseline in HAQ-DI, enthesitis, dactylitis, SF-36 PCS/MCS scores at wk14; and ACR50 and change from baseline in total modified vdH-S (structural damage) score at wk24. Efficacy analyses were based on randomized treatment. Adverse events (AE) through wk24 are reported here. Investigators remain blinded through wk60. Results: 480 pts were randomized (PBO: 239; GLM: 241). The study met its primary and all controlled secondary endpoints. At wk14, significantly greater proportions of GLM pts vs PBO achieved ACR20 (75.1% vs. 21.8%). Also, GLM treatment resulted in significant change from baseline HAQ-DI score (-0.60 vs. -0.12), ACR50 (43.6% vs. 6.3%), PASI 75 (59.2% vs. 13.6%), ACR70 (24.5% vs. 2.1%), change from baseline in enthesitis and dactylitis scores (-1.8 vs. -0.8 and -7.8 vs. -2.8, respectively), and change from baseline in SF-36 PCS and SF-36 MCS scores (8.65 vs. 2.69 and 5.33 vs. 0.97, respectively) (all p<0.001) at wk14. At wk24, significantly greater proportions of GLM pts vs. PBO pts achieved ACR 50 (53.5% vs. 6.3%, p<0.001). At wk24, there was significantly less progression of structural damage for GLM pts vs PBO as measured by change from baseline in total modified vdH-S score (-0.36 vs. 1.95; p<0.001). ACR20 was significantly higher with GLM than PBO as early as wk2 (45.6% vs. 7.5%; p<0.001). 27.0% of GLM pts (vs. 4.2% PBO) achieved Minimal Disease Activity by wk14. Due to the difference in response rates in GLM vs. PBO treated pts, the number needed to treat for ACR20 at wk14 was 1.9 in a post-hoc analysis (Table). Through wk24, 46.3% of GLM pts and 40.6% of PBO pts had ≥1 AE; 2.9% vs. 3.3% of pts, respectively, had ≥1 serious AE. Two deaths, 2 malignancies, and 1 demyelinating event were reported. The most common treatment-emergent type of AE was infection (20.0% of GLM pts vs. 13.8% of PBO pts). No opportunistic infection or tuberculosis was reported through wk24. The rate of infusion reactions was low at <2%; none was serious or severe. Conclusions: In pts with active PsA, IV GLM demonstrated significant and clinically meaningful improvements of disease activity and physical function, skin psoriasis clearance, HRQoL, reduction in dactylitis and enthesitis, and inhibition of structural damage progression. GLM was well-tolerated through wk24; the safety profile was consistent with other anti-TNF therapies, including SC GLM. Disclosure of Interest: A. Kavanaugh Consultant for: Janssen, M. E. Husni Consultant for: Janssen, UCB, Amgen, Novartis, Lilly, Regeneron, D. Harrison Employee of: Janssen Research & Development, LLC, L. Kim Employee of: Janssen Research & Development, LLC, K. H. Lo Employee of: Janssen Research & Development, LLC, E. Hsia Employee of: Janssen Research & Development, LLC